Constraints on the Emplacement of Martian Nakhlite Igneous Rocks and Their Source Volcano From Advanced Micro‐Petrofabric Analysis. Issue 6 (4th June 2022) - Griffin, S.; Daly, L.; Keller, T.; Piazolo, S.; Forman, L. V.; Lee, M. R.; Baumgartner, R. J.; Trimby, P. W.; Benedix, G. K.; Irving, A. J.; Hoefnagels, B.
Abstract: The Martian nakhlite meteorites, which represent multiple events that belong to a single magma source region represent a key opportunity to study the evolution of Martian petrogenesis. Here 16 of the 26 identified nakhlite specimens are studied using coupled electron backscatter diffraction (EBSD) and emplacement end‐member calculations. EBSD was used to determine shape preferred orientation of contained augite (high Ca‐clinopyroxene) phenocrysts by considering their crystallographic preferred orientation (CPO). Parameters derived from EBSD, and energy dispersive X‐ray spectroscopy spectra were used in basic emplacement models to assess their dominant mechanism against three end‐member scenarios: thermal diffusion, crystal settling, and crystal convection. Results from CPO analyses indicate low intensity weak‐moderate CPO. In all samples, a consistent foliation within the <001> axes of augite are observed typically coupled with a weaker lineation CPO in one of the other crystallographic axes. These CPO results agree best with crystal settling being the dominant emplacement mechanism for the nakhlites. Modeled crystal settling results identify two distinguishable groups outside of the model's resolution indicating the presence of secondary emplacement mechanisms. Comparison of the two identified groups against CPO, geochemical, and age parameters indicate random variability between individual meteorites. Therefore, coupled CPO and emplacement modeling results identify an overarching characteristic of a dominant crystal settling emplacement mechanism for the nakhlite source volcano despite exhibiting random variation with each discharge through time. Plain Language Summary: A group of Martian meteorites known as the nakhlites was investigated to better understand volcanism on Mars by using the specialist microscopy technique of electron backscatter diffraction and basic modeling of known igneous processes. The presented data suggest that the magma that was discharged from the nakhlite source volcano varied randomly through time but solidified into rocks via a consistent dominant mechanism of crystal settling. These findings show Martian volcanism is dynamic, where individual eruptions are variable, yet retain overarching volcanic source characteristics that can be identified from large studies of multiple samples. Key Points: S‐type to LS‐type crystallographic preferred orientation (CPO) identified in the nakhlites CPO indicate nakhlite formation in environments characteristic of crystal settling CPO and emplacement modeling suggest random variation in discharge through time with overarching consistent emplacement